Nkx2.5: a crucial regulator of cardiac development, regeneration and diseases - Cao, Ce; Li, Lei; Zhang, Qian; Li, Haoran; Wang, Ziyan; Wang, Aoao; Liu, Jianxun (Frontiers in Cardiovascular Medicine, 2023)
Cardiomyocytes fail to regenerate after birth and respond to mitotic signals through cellular hypertrophy rather than cellular proliferation. Necrotic cardiomyocytes in the infarcted ventricular tissue are eventually replaced by fibroblasts, generating scar tissue. Cardiomyocyte loss causes localized systolic dysfunction. Therefore, achieving the regeneration of cardiomyocytes is of great significance for cardiac function and development. Heart development is a complex biological process. An integral cardiac developmental network plays a decisive role in the regeneration of cardiomyocytes. During this process, genetic epigenetic factors, transcription factors, signaling pathways and small RNAs are involved in regulating the developmental process of the heart. Cardiomyocyte-specific genes largely promote myocardial regeneration, among which the Nkx2.5 transcription factor is one of the earliest markers of cardiac progenitor cells, and the loss or overexpression of Nkx2.5 affects cardiac development and is a promising candidate factor. Nkx2.5 affects the development and function of the heart through its multiple functional domains. However, until now, the specific mechanism of Nkx2.5 in cardiac development and regeneration is not been fully understood. Therefore, this article will review the molecular structure, function and interaction regulation of Nkx2.5 to provide a new direction for cardiac development and the treatment of heart regeneration.